Dispute processes : ADR and primary forms of decision-making - Palmer, Michael J. E., 1944-; Roberts, Simon (Simon A.) (The law in context series, 2020)
"The International Journal of Law in Context is the companion journal to the Law in Context book series and provides a forum for interdisciplinary legal studies and offers intellectual space for ground-breaking critical research. It publishes contextual work about law and its relationship with other disciplines including but not limited to science, literature, humanities, philosophy, sociology, psychology, ethics, history and geography. More information about the journal and how to submit an article can be found at http://journals.cambridge.org/ijc"--